2006
DOI: 10.1152/japplphysiol.01267.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Muscle size and strength are increased following walk training with restricted venous blood flow from the leg muscle, Kaatsu-walk training

Abstract: Previous studies have shown that low-intensity resistance training with restricted muscular venous blood flow (Kaatsu) causes muscle hypertrophy and strength gain. To investigate the effects of daily physical activity combined with Kaatsu, we examined the acute and chronic effects of walk training with and without Kaatsu on MRI-measured muscle size and maximum dynamic (one repetition maximum) and isometric strength, along with blood hormonal parameters. Nine men performed Kaatsu-walk training, and nine men per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
602
5
41

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 517 publications
(673 citation statements)
references
References 20 publications
25
602
5
41
Order By: Relevance
“…The CSA of the thigh muscle and strength significantly increased only for the BFR group. Considering the conventional findings of the walking study, showing that older adults and about a 6-month period are requirements for observing hypertrophy, the findings of Abe et al (2006) clearly demonstrated the potential of BFR. Not surprisingly, 6-10 weeks of walk training with BFR was effective in increasing muscle size for older adults 52,53) .…”
Section: Training With Blood Flow Restriction (Bfr)mentioning
confidence: 80%
See 2 more Smart Citations
“…The CSA of the thigh muscle and strength significantly increased only for the BFR group. Considering the conventional findings of the walking study, showing that older adults and about a 6-month period are requirements for observing hypertrophy, the findings of Abe et al (2006) clearly demonstrated the potential of BFR. Not surprisingly, 6-10 weeks of walk training with BFR was effective in increasing muscle size for older adults 52,53) .…”
Section: Training With Blood Flow Restriction (Bfr)mentioning
confidence: 80%
“…One reason for the absence of the hypertrophic effect in young adults is that these studies employed overly short training periods (3 weeks) [58][59][60] . A further explanation could be that young adults tend to be active and strong compared to older adults, so that walking does not turn out to be a sufficient exercise stimulus for hypertrophy.…”
Section: Muscle Hypertrophy With Endurance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging has often been associated with hyposecretion of growth hormone (GH), and GH hyposecretion has been associated with muscle atrophy and depressive symptoms, thereby affecting patients QOL (Hull and Harvey, 2003). Although it is unclear how KAATSU exercise induces enhanced muscle strength and the mechanism of myopachynsis, it has been shown that a significant increase in GH level is observed immediately after KAATSU exercise (Takarada et al, 2000a;Takano et al, 2005;Abe et al, 2006). This observation indicates the possible involvement of increased GH level in the mechanism of myopachynsis in BFS patients.…”
Section: Discussionmentioning
confidence: 99%
“…For treatment, exercise therapy may be performed, but no effective rehabilitation program has been established. KAATSU exercise, a novel, attention-drawing method of low-intensity resistance exercise performed under the condition of restricting muscle blood flow (Takarada et al, 2000b;Abe et al, 2006;Karabulut et al, 2007;Wernbom et al, 2008), causes minimal strain on the musculoskeletal and cardiovascular systems compared to high-intensity resistance exercise and thus is increasingly applied to rehabilitation programs for patients with various disorders. Meanwhile, its effect on BFS patients has yet to be examined.…”
Section: Introductionmentioning
confidence: 99%